Factors influencing retirement planning behaviour among staff in Majlis Daerah Kampar / Norul Idayu A Azmi - A Azmi, Norul Idayu (Faculty of Business and Management, UiTM Johor, 2019)
Retirement planning is necessary for people in order to ensure that an individual have enough funds to support the life after retirement to support themselves as well as their family. The basic needs for planning on retirement is for the daily expenses, cost of medical, emergencies need and most importantly is for the outstanding loan. This research will study about the retirement planning behaviour among staff in Majlis Daerah Kampar, Perak. Retirement planning is a rising issue that need to be taken seriously by the individuals because it related to the future issue which are their income is enough or not to support their live after retirement especially in the unexpected event as well as their health problems. This research study on three independent variables that are goal clarity, attitude and potential conflict in retirement. The questionnaires will be distributed to 155 respondents and the population in this research is staff in Majlis Daerah Kampar. A random sampling method through personally administered questionnaires. This research applied some basic methodologies for the analysis such as descriptive, reliability and validity, correlation and multiple regression. This research also will be using Statistical Package for Social Science (SPSS) software to analyse the result based on the questionnaires given to the respondents.